Cognitive-behavioural interventions for atte ntion deﬁcithyperactivity disorder (ADHD) in adults - Lopez, Pablo Luis (2013)
According to the Diagnostic and Statistical Manual for MentalDisorders (DSM-IV-TR), attention deficit hyperactivity disorder(ADHD) is a developmental condition characterised by symptomsof inattention, hyperactivity and impulsivity (APA 2000). Usingthese criteria, ADHD can be divided into three types: combinedtype, predominantly inattentive type and predominantly hyperactive-impulsive type. The International Classification of Diseases(ICD-10) offers a similar definition for hyperkinetic disorders(WHO 1992). Along with these threemain symptomatic clusters,people with ADHD also present with deficits in executive functions,behaviour and emotion regulation, and motivation (Brown2000; Wender 2001; Davidson 2008; Torrente 2011). There is ahigh prevalence of comorbid disorders, estimated at 50% to 75%(Kessler 2006), including anxiety, depression and substance abuse(Biederman 1993; Murphy 1996). Epidemiological studies estimatethat the prevalence of ADHD is around 5% in childhood(Polanczyk 2007) and approximately 2.5% in adulthood (Simon2009).